Correlation Between 11th Batch Iai Al-Azis Students' Understanding of Usury In Sharia and Buya Hamka's Tafsir - Nahlia Puteri Madini; Shofi Eka Romandhoni; Saskiah Amanah; Amirudin; Fitri Rachmiati Sunarya (South Sulawesi Education Development (SSED), 2024)
The concept of usury (riba) remains a critical issue in the context of Islamic economics, with its prohibition deeply rooted in Islamic principles. This study examines the understanding of usury among the 11th batch of students at Institut Agama Islam Al-Zaytun Indonesia (IAI AL-AZIS) and its correlation with Buya Hamka's interpretations. The research focuses on assessing students' comprehension of the definitions, classifications, and impacts of usury from a Sharia perspective, as well as their awareness of its practical implications. Using a quantitative survey method, data was collected from 56 students across six study programs through questionnaires. The results indicate varying levels of understanding, with 73.2% of respondents demonstrating knowledge of usury in Islam, while others were uncertain or unaware. The findings underscore the influence of education, social environment, and access to religious knowledge on students' understanding. Buya Hamka’s interpretations, emphasizing usury as a form of exploitation and economic injustice, align with the Islamic prohibition of interest-based transactions. However, gaps in students’ knowledge reveal the need for improved educational strategies to promote Sharia-compliant financial practices. Recommendations include integrating Islamic finance principles into curricula, employing interactive teaching methods, and fostering greater awareness of ethical financial alternatives. This study highlights the importance of enhancing Islamic economic education to ensure adherence to Sharia principles and the promotion of equitable economic practices.